Pesniške, mentalne in druge podobe - Pavlič, Darja (Primerjalna književnost, 2010)
After briefly outlining the use of various collective terms denoting metaphors, comparisons, symbols, and other poetic means, this article primarily deals with the relation between poetic and mental images in addition to exploring the original meaning of the term image.
Keywords: literarna veda; literary science; podobje; pesniške podobe; mentalne podobe; zaznavanje; metafora; metaphor; simbol